Traditional food patterns are associated with better diet quality and improved dietary adequacy in Aboriginal peoples in the Northwest Territories, Canada. Issue 3 (22nd May 2014) - Sheehy, T.; Kolahdooz, F.; Schaefer, S. E.; Douglas, D. N.; Corriveau, A.; Sharma, S.
Abstract Background Traditionally, the Arctic diet has been derived entirely from locally harvested animal and plant species; however, in recent decades, imported foods purchased from grocery stores have become widely available. The present study aimed to examine Inuvialuit, traditional or nontraditional dietary patterns; nutrient density of the diet; dietary adequacy; and main food sources of energy and selected nutrient intakes. Methods This cross‐sectional study used a culturally appropriate quantitative food frequency questionnaire to assess diet. Traditional and nontraditional eaters were classified as those consuming more or less than 300 g of traditional food daily. Nutrient densities per 4184 kJ (1000 kcal) were determined. Dietary adequacy was determined by comparing participants' nutrient intakes with the Dietary Reference Intakes. Results The diet of nontraditional eaters contained, on average, a lower density of protein, niacin, vitamin B12, iron, selenium, zinc, omega‐3 fatty acids (P ≤ 0.0001), vitamin B6, potassium, thiamin, pantothenic acid (P ≤ 0.001), riboflavin and magnesium (P ≤ 0.05). Inadequate nutrient intake was more common among nontraditional eaters for calcium, folate, vitamin C, zinc, thiamin, pantothenic acid, vitamin K, magnesium, potassium and sodium. Non‐nutrient‐dense foods (i.e. high fat and high sugar foods) contributed to energy intake in both groups, more so among nontraditional eaters (45% versus 33%). Traditional foods accounted for 3.3% and 20.7% of total energy intake among nontraditional and traditional eaters, respectively. Conclusions Diet quality and dietary adequacy were better among Inuvialuit who consumed more traditional foods. The promotion of traditional foods should be incorporated in dietary interventions for this population.